• "When solving systems by substitution use the following steps: 1. Solve one of the equations for a variable 2. Substitute for the variable in the other equation and solve. 3. Substitute for and solve for the remaining variable" Source and further information: Implementation: 1. solve [x+2y=10] for x: x=10-2y 2. substitute x in the other equation: 3(10-2y)-y=2 ...and solve: 30-6y-y=2 7y=28 y=4 3. substitute y in [x=10-2y]: x=10-2*4 x=10-8 x=2
  • Who is asking this question? We both need help on the same thing..Where do u got to school?

Copyright 2023, Wired Ivy, LLC

Answerbag | Terms of Service | Privacy Policy